Phase 1/2 study of fractionated dose lutetium‐177–labeled anti–prostate‐specific membrane antigen monoclonal antibody J591 (177Lu‐J591) for metastatic castration‐resistant prostate cancer. Issue 15 (23rd April 2019) - Tagawa, Scott T.; Vallabhajosula, Shankar; Christos, Paul J.; Jhanwar, Yuliya S.; Batra, Jaspreet S.; Lam, Linda; Osborne, Joseph; Beltran, Himisha; Molina, Ana M.; Goldsmith, Stanley J.; Bander, Neil H.; Nanus, David M.
Abstract : Background: Prostate cancer is radiosensitive. Prostate‐specific membrane antigen (PSMA) is selectively overexpressed on advanced, castration‐resistant tumors. Lutetium‐177–labeled anti‐PSMA monoclonal antibody J591 ( 177 Lu‐J591) targets prostate cancer with efficacy and dose‐response/toxicity data when delivered as a single dose. Dose fractionation may allow higher doses to be administered safely. Method: Men with metastatic castration‐resistant prostate cancer refractory to or refusing standard treatment options with normal neutrophil and platelet counts were enrolled in initial phase 1b dose‐escalation cohorts followed by phase 2a cohorts treated at recommended phase 2 doses (RP2Ds) comprising 2 fractionated doses of 177 Lu‐J591 2 weeks apart. 177 Lu‐J591 imaging was performed after treatment, but no selection for PSMA expression was performed before enrollment. Phase 2 patients had circulating tumor cell (CTC) counts assessed before and after treatment. Results: Forty‐nine men received fractionated doses of 177 Lu‐J591 ranging from 20 to 45 mCi/m 2 ×2 two weeks apart. The dose‐limiting toxicity in phase 1 was neutropenia. The RP2Ds were 40 mCi/m 2 and 45 mCi/m 2 ×2. At the highest RP2D (45 mCi/m 2 ×2), 35.3% of patients had reversible grade 4 neutropenia, and 58.8% of patients had thrombocytopenia. This dose showed a greater decrease in prostate‐specific antigen (PSA) levels and longer survival (87.5% with any PSA decrease, 58.8% with >30% decrease, 29.4% with >50% decrease; median survival, 42.3 months [95% confidence interval, 19.9‐64.7]). Fourteen of 17 (82%) patients with detectable CTCs experienced a decrease in CTC count. Overall, 79.6% of patients had positive PSMA imaging; those with less intense PSMA imaging tended to have poorer responses. Conclusion: Fractionated administration of 177 Lu‐J591 allowed higher cumulative radiation dosing. The frequency and depth of PSA decrease, overall survival, and toxicity (dose‐limiting myelosuppression) increased with higher doses. Abstract : Administration of 177 Lu‐J591 with dose fractionation allows higher cumulative radioactivity dosing. The frequency and depth of prostate‐specific antigen decrease, overall survival, and toxicity (dose‐limiting myelosuppression) increases with higher doses.